2018
DOI: 10.1016/j.disc.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Improved FPT algorithms for weighted independent set in bull-free graphs

Abstract: Abstract. Very recently, Thomassé, Trotignon and Vuskovic [WG 2014] have given an FPT algorithm for Weighted Independent Set in bull-free graphs parameterized by the weight of the solution, running in time 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Special cases of this variant are studied in the literature. For example, [5,18,7] study the parameterized problem of finding a clique in a weighted graph, where the parameter is the target value.…”
Section: P-size-cspmentioning
confidence: 99%
See 1 more Smart Citation
“…Special cases of this variant are studied in the literature. For example, [5,18,7] study the parameterized problem of finding a clique in a weighted graph, where the parameter is the target value.…”
Section: P-size-cspmentioning
confidence: 99%
“…They also prove that the weighted variant of p-Clique is in W [1]. Notice that here the parameter is the size of the clique, thus it is a substantially weaker parameterization than that of [5,18,7]. Generalizing this problem in the language of CSP, for every computable function f : N → N, we introduce the Parameterized Weighted CSP:…”
Section: P-size-cspmentioning
confidence: 99%
“…Dabrowski et al showed that MIS is FPT 2 in H-free graphs, for all H on four vertices, except H = C 4 (the cycle on four vertices). Thomassé et al presented an FPT algorithm on bull-free graphs [37], whose running time was later improved by Perret du Cray and Sau [17]. Bonnet et al provided three variants of a parameterized counterpart of Alekseev's reduction [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…On the negative side, it was proved that MIS remains W [1]-hard in K 1,4 -free graphs [16] Finally, we can also mention the case where H is the bull graph, which is a triangle with a pending vertex attached to two different vertices. For that case, a polynomial Turing kernel was obtained [22] then improved [13].…”
Section: Introductionmentioning
confidence: 99%